A soccer match`s ability to enhance lymphocyte capability to produce ROS and induce oxidative damage - Ferrer, M. D.; Tauler, P.; Sureda, A.; Pujol, P.; Dorobnic, F.; Tur, J. A.; Pons, A. (International Journal of Sport Nutrition and Exercise Metabolism, 2009)
Soccer-associated oxidative stress has barely been studied. The aims of this study were to establish the effect of a soccer training match and the effect of a diet supplementation with a multivitamin complex and coenzyme Q during 3 months of soccer training on the pro-oxidant and antioxidant status of lymphocytes. In a randomized, double-blind trial, 19 male preprofessional soccer players were treated with either an antioxidant nutrient cocktail or placebo for 90 days. After this period the athletes played a soccer match lasting 60 min. All determinations were made under basal conditions before and after the training period and after the match. Basal lymphocyte hydrogen peroxide (H2O2) production did not change after the 3 months of training. Catalase activity decreased (about 50%) after the 3 months, whereas glutathione reductase increased its activity (150-200%) both with placebo and in the supplemented group. Basal ascorbate levels were maintained during the training period, whereas a-tocopherol and MDA decreased (about 40%) in both groups. The match increased H2O2production (180%) in both groups when the lymphocytes were stimulated with phorbol myristate acetate, and it also increased MDA levels (150%). Antioxidant enzyme activities and antioxidant vitamin levels were maintained before and after the match. Regular soccer training modifies the lymphocyte strategy to eliminate ROS and increases protection against oxidative damage. A friendly soccer match raises lymphocyte capacity to produce ROS and oxidative damage, but it is not enough to induce a defensive response, thus leading to a situation of postexercise oxidative stress. Supplementation with low doses of antioxidant vitamins and coenzyme Q does not modify the endogenous antioxidant response to training.